2020
DOI: 10.3389/fimmu.2020.00237
|View full text |Cite
|
Sign up to set email alerts
|

CpG Oligonucleotides Protect Mice From Alphavirus Encephalitis: Role of NK Cells, Interferons, and TNF

Abstract: Arboviruses including alphavirus are responsible for most emerging infectious diseases worldwide. Recent outbreaks of chikungunya virus serve as a stark reminder to their pathogenic potential. There are no vaccines or therapeutics currently available to contain alphavirus outbreaks. In this study we evaluated the effect of immunomodulatory CpG ODN on the clinical progression of neurotropic Sindbis virus infection. Neonatal C57Bl-6 mice challenged with Sindbis virus AR339 (25 PFU Subcutaneous) infect neurons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…As mentioned above, CpG-ODN can activate and enhance NK cell function, a characteristic that some authors have associated with enhanced anti-viral properties. For instance, CpG-ODN has been shown to effectively fight alphavirus encephalitis in neonatal mice ( 162 ). Moreover, CpG-ODN has also been shown to be efficacious as an adjuvant in vaccines against viruses, for example, by generating a humoral protective response to the HBV surface antigen HBsAg ( 88 ), which subsequently lead to the development of an FDA-approved vaccine against HBV that was superior compared to an established aluminum hydroxide-based HBV vaccine ( 120 ).…”
Section: Cpg-odn – Safety Considerations and Other Applicationsmentioning
confidence: 99%
“…As mentioned above, CpG-ODN can activate and enhance NK cell function, a characteristic that some authors have associated with enhanced anti-viral properties. For instance, CpG-ODN has been shown to effectively fight alphavirus encephalitis in neonatal mice ( 162 ). Moreover, CpG-ODN has also been shown to be efficacious as an adjuvant in vaccines against viruses, for example, by generating a humoral protective response to the HBV surface antigen HBsAg ( 88 ), which subsequently lead to the development of an FDA-approved vaccine against HBV that was superior compared to an established aluminum hydroxide-based HBV vaccine ( 120 ).…”
Section: Cpg-odn – Safety Considerations and Other Applicationsmentioning
confidence: 99%
“…Altered NK cells underlie the severe ZIKV infection in LILRB4-deficient mice. Although the number of NK cells infiltrating the CNS was lower than that of T cells (Figure 2F), they can play a key role in viral clearance by killing infected cells through exocytosis of cytolytic granules containing perforin and granzyme, or by secreting proinflammatory cytokines, in particular IFN-γ, and are therefore considered the first line of defense against viral infection such as DENV and Sindbis virus (34)(35)(36). Using antibodies against NK1.1 to deplete NK cells in vivo, we confirmed that these cells play a critical role in protection against meningoencephalitis by ZIKV, as mice lacking NK cells had higher viral load in the brain and increased mortality (Supplemental Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Neonatal mice have increased susceptibility to viruses and develop symptomatic infections when challenged with Alpha-, Arena- and Flavi-viruses, even when the adults of the same strain are resistant ( 18 , 19 , 23 , 33 35 ). As expected, neonatal hACE2 tg mice succumbed following a SARS-CoV-2 (10 2 -10 5 TCID 50 Washington 2020 isolate, IN) challenge in a dose-dependent manner ( Figures 1A–D and Supplementary Figure 2F ) and high titer virus were evident in the lungs and brain of mice challenged IN with 10 5 TCID 50 as determined by viral RNA levels and TCID 50 ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…This is different from challenges with the parental VSV or from rVSV expressing the Ebola Zaire glycoproteins as previously shown ( 18 ). The increased susceptibility of neonatal mice to viral infections is well established ( 18 , 23 , 34 , 35 , 45 , 46 ). This extends to coronaviruses where reports show the acquisition of virulence in young, but not aged, mice through serial passage of SARS-CoV Urbani strain ( 47 ).…”
Section: Discussionmentioning
confidence: 99%